Kekuatan Geser Panel Kayu Vertikal Dengan Perkuatan Single Bracing Tulangan Baja Akibat Pembebanan Siklik - Monika, Fanny (Semesta Teknika, 2016)
PanelsÂ in wooden construction serve as walls as well as providing structural lateralÂ resistanceÂ againstÂ earthquakeÂ ifÂ designed well. Panel materialsÂ consist of frames withÂ sheathingsÂ suchÂ asÂ PlywoodÂ or Oriented Strand Board(OSB)Â connectedÂ toÂ woodenÂ frames with nails as connectors. Lateral force of the panels can be increased, for example by adding diagonal rods/bracings to the frames. In this study a woodenÂ panel which was Sengon wooden panel connected to Laminated Veneer Lumber(LVL) wooden panel with CN 50 nails withÂ a diameter of 2,8 mm andÂ the distance betweenÂ the nails was 240 mm with plainÂ steelÂ reinforcementÂ single bracing with a diameter of 8 mm in pull position using corner plate as a connector between bracing and LVL wooden panel. CyclicÂ test had 20%Îy,Â 40%Îy,Â 60%ÎyÂ deformation controlsÂ andÂ loaded with monotonicÂ until wooden panels collapsed. TheÂ results of cyclicÂ testÂ inÂ stableÂ conditionÂ 60%Îy had equivalent viscous damping ratio values of 8,324%.Â FailuresÂ inÂ panelsÂ oftenÂ happenedÂ toÂ connectingÂ nails,Â cornerÂ plates,Â and steelÂ bracings. TheÂ typesÂ ofÂ failure were NailÂ Pull-ThroughÂ ofÂ Sheathing,Â Pull-ThroughÂ SheathingÂ Failures,Â MudsillÂ Failure,Â bucklingÂ onÂ cornerÂ plates,Â and buckling on steel bracingsÂ